Hasil Belajar Siswa Pada Materi Luas Jajargenjang Menggunakan Model Pembelajaran Generatif di Kelas VII SMP - Pratamasari, Feramulya; Nery, Rieno Septra; Supriadi, Agus (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2024)
This study aims to determine whether there is an effect of the generative learning model on students' learning outcomes in mathematics, specifically on the topic of parallelogram area, in seventh-grade students at a junior high school (SMP). This research is experimental in nature. The population consists of all seventh-grade students, with class VII.6 serving as the experimental group and class VII.7 as the control group. The results show that students who used the generative learning model achieved an average score of = 83,475 with a standard deviation of s1 = 10,679, whereas students who did not use the model had an average score of = 74,425 with a standard deviation of s2 = 12,5450. After analyzing the data, a difference in average scores between the experimental and control groups was found. Based on statistical analysis using the t-test, the results showed tcalculated = 3.474 for ? = 5% (? = 0.05) and degrees of freedom (df) = 78, with ttable = 1.980. Since tcalculated > ttable, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. The hypothesis test confirms that "there is an effect of the generative learning model on students' learning outcomes in mathematics on the topic of parallelogram area in seventh-grade students at a junior high school (SMP)."